Association of menopausal characteristics and risk of coronary heart disease: a pan-European case–cohort analysis. (22nd February 2019) - Dam, Veerle; van der Schouw, Yvonne T; Onland-Moret, N Charlotte; Groenwold, Rolf H H; Peters, Sanne A E; Burgess, Stephen; Wood, Angela M; Chirlaque, Maria-Dolores; Moons, Karel G M; Oliver-Williams, Clare; Schuit, Ewoud; Tikk, Kaja; et al.
Abstract: Background: Earlier age at menopause has been associated with increased risk of coronary heart disease (CHD), but the shape of association and role of established cardiovascular risk factors remain unclear. Therefore, we examined the associations between menopausal characteristics and CHD risk; the shape of the association between age at menopause and CHD risk; and the extent to which these associations are explained by established cardiovascular risk factors. Methods: We used data from EPIC-CVD, a case–cohort study, which includes data from 23 centres from 10 European countries. We included only women, of whom 10 880 comprise the randomly selected sub-cohort, supplemented with 4522 cases outside the sub-cohort. We conducted Prentice-weighted Cox proportional hazards regressions with age as the underlying time scale, stratified by country and adjusted for relevant confounders. Results: After confounder and intermediate adjustment, post-menopausal women were not at higher CHD risk compared with pre-menopausal women. Among post-menopausal women, earlier menopause was linearly associated with higher CHD risk [HRconfounder and intermediate adjusted per-year decrease = 1.02, 95% confidence interval (CI) = 1.01–1.03, p  = 0.001]. Women with a surgical menopause were at higher risk of CHD compared with those with natural menopause (HRconfounder-adjusted  = 1.25, 95% CI = 1.10–1.42, p  < 0.001), but this attenuated after additional adjustment for age at menopause and intermediates (HR = 1.12, 95% CI = 0.96–1.29, p  = 0.15). A proportion of the association was explained by cardiovascular risk factors. Conclusions: Earlier and surgical menopause were associated with higher CHD risk. These associations could partially be explained by differences in conventional cardiovascular risk factors. These women might benefit from close monitoring of cardiovascular risk factors and disease.